Analisis Penegakan Hukum terhadap Pelanggaran Keimigrasian oleh Pelintas Batas dari Papua Nugini ke Indonesia - Al Lutfiah, Elsya; Irayadi, Muhammad (LPPM Iblam School of Law, 2024)
Enforcement of immigration law violations by cross-border travelers from Papua New Guinea to Indonesia poses a significant challenge for the state authorities, especially in ensuring the security and sovereignty of border areas. These immigration violations are often driven by social, cultural, and economic factors influencing the behavior of border communities. This study aims to analyze the implementation of immigration regulations in border areas and the challenges faced in law enforcement. The findings reveal that infrastructure limitations, human resources, and lack of inter-agency coordination are the main barriers to effective law enforcement.This research employs a qualitative method with a normative legal approach, relying on primary and secondary data obtained through library research. The analytical approach used is descriptive qualitative, classifying legal materials into three main categories: primary, secondary, and tertiary. The results of the study show that despite efforts in surveillance through joint patrols and infrastructure improvements, the effectiveness of law enforcement in the Indonesia-Papua New Guinea border remains limited. Many cross-border travelers still use unofficial routes, and the public's understanding of immigration regulations remains low. This study recommends improving coordination between law enforcement agencies and enhancing legal outreach to border communities